Mouthwashes: An in vitro study of their action on microbial biofilms and cytotoxicity to gingival fibroblasts - De Oliveira, Jonatas Rafael [UNESP]; Belato, Kely Karina [UNESP]; De Oliveira, Felipe Eduardo [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; De Oliveira, Luciane Dias [UNESP] (My University, 2018)
This study evaluated the in vitro antibiofilm effect of 5 different commercial mouthwashes (Cepacol Traditional, Colgate Plax Fresh Mint, Listerine Cool Mint, Oral-B Complete, and Sensodyne) on Candida albicans, Staphylococcus aureus, Enterococcus faecalis, Streptococcus mutans, Escherichia coli, and Pseudomonas aeruginosa. The cytotoxic effect of the mouthwashes on gingival fibroblasts was also analyzed. A colorimetric assay with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was used to investigate the viability of biofilms after 48 hours and gingival fibroblasts after 24 hours. The biofilms were exposed to the mouthwashes for 2 different lengths of time: T1, the time recommended by the manufacturer (30 or 60 seconds); and T2, double the recommended time (60 or 120 seconds). All antiseptic mouthwashes caused a significant reduction of biofilm (P < 0.05) as well as a significant reduction of viable gingival fibroblasts (P < 0.05) with both exposure times (T1 and T2). It can be concluded that the commercial mouthwashes demonstrated effective antibiofilm activity; they were more effective on bacteria than on C albicans. A significant cytotoxic effect on gingival fibroblasts was also observed.